Pendidikan Islam di Era Industri 4.0 (Studi Analisis Terhadap Tantangan Profesionalisme Guru Pendidikan Agama Islam) - Rofiqi, Rofiqi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
The existence of industry era 4.0 brings significant impact in education especially for professionalism of teacher. Era industry and its development offers various simplicities, however it endangers the existence of qualified professional that is teacher. Various dilemmas and challenges of Islamic education drive in and out of problems. In addition, it causes internal education factor which cannot be solved. Islamic education is also confronted by complexity issues post-appearance industry era 4.0, therefore an issue of professionalism of teacher should be solved by improving teacher competency. It refers to the pedagogies development, information technique competency, personal competency, and social competency. Furthermore, the teacher should have good creativity, productivity, strong work ethic, and high commitment in carrying on their carrier as teacher. Through training session, the teacher is demanded to be able to contribute positive provision to the leaners with knowledge, instilling high discipline, reactiveness, innovativeness, and competitiveness.